The Outcome of Anaplastic Glioma Treated at a Tertiary Cancer Care Institute in South Asia - Natarajan, Arunkumar Madukkarai; Radhakrishnan, Venkatraman; John, Alexander (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: Anaplastic glioma is an aggressive brain tumor frequently diagnosed in young adults. Data on anaplastic gliomas from India is limited. This study aimed to evaluate prognostic factors of anaplastic glioma and correlate them with patient outcomes. Materials and methods: This retrospective observational study included 57 patients with anaplastic glioma treated at a cancer institute in Chennai, India, between 1996 and 2015. Data was extracted from the institute’s hospital-based electronic health record tumor registry. Factors analyzed included age, sex, histology, tumor location, type of surgery, adjuvant treatment, and radiation treatment technique. Progression-free survival (PFS) and overall survival (OS) were calculated using the Statistical Package for Social Sciences (SPSS) software. Result: The median follow-up time was 34 months. The median PFS and OS were 28 and 41 months, respectively. Univariate analysis showed that improved survival was associated with anaplastic oligodendroglioma histology (HR 0.43, CI 0.22-0.80, p = 0.006), frontal lobe location (HR 1.96, CI 1.07-3.58, p = 0.025), gross total resection (HR 1.94, CI 1.03-3.64, p = 0.034), and the addition of temozolomide (HR 2.09, CI 1.14-3.84, p = 0.014). Multivariate analysis confirmed that anaplastic oligodendroglioma histology (HR 0.49, CI 0.25-0.95, p = 0.037), frontal lobe location (HR 2.14, CI 1.12-4.07, p = 0.021), gross total resection (HR 2.89, CI 1.47-5.69, p = 0.002), and the addition of temozolomide (HR 2.02, CI 1.07-3.81, p = 0.029) remained significant factors for improved OS. Conclusion: This study reveales that anaplastic oligodendroglioma histology, frontal lobe location, gross total resection, and the addition of temozolomide chemotherapy to radiation are associated with improved outcomes for patients with anaplastic glioma. These factors should be considered when planning treatment strategies for this challenging disease.